Pioglitazone, a PPAR-γ Activator, Stimulates BKCa but Suppresses IKM in Hippocampal Neurons - Chen, Tsang-Shan; Lai, Ming-Chi; Hung, Te-Yu; Lin, Kao-Min; Huang, Chin-Wei; Wu, Sheng-Nan (Frontiers in Pharmacology, 2018)
Pioglitazone (PIO), a thiazolidinedone, was reported to stimulate peroxisome proliferator-activated receptor-gamma (PPAR-gamma) with anti-inflammatory, anti-proliferative, anti-diabetic and antidepressive activities. However, whether this compound exerts any perturbations on Ca2+-activated K+ and M-type K+ currents in central neurons remains largely unresolved. In this study, we investigated the effects of PIO on these potassium currents in hippocampal neurons (mHippoE-14). In whole-cell current recordings, the presence of PIO (10 microM) increased the amplitude of Ca2+-activated K+ current (IK(Ca)) in mHippoE-14 cells. PIO-induced stimulation of IK(Ca) observed in these cells was reversed by subsequent addition of paxilline, yet not by TRAM-39 or apamin. In inside-out current recordings, PIO applied to the bath concentration-dependently increased the activity of large-conductance Ca2+-activated K+ (BKCa) channels with an EC50 value of 7.6 microM. Its activation of BKCa channels in mHippoE-14 cells was voltage-dependent and accompanied by both a lengthening in mean open time and a shortening in slow component of mean closed time. The activation curve of BKCa channels after addition of PIO was shifted to less depolarized potential without any change in the gating charge. PIO also suppressed the amplitude of M-type K+ currents inherently in mHippoE-14 neurons. Taken together, in addition to its agonistic action on PPAR-gamma, PIO-induced perturbation of these potassium channels may be responsible for its widely pharmacological actions on hippocampal neurons.